Ochrona danych osobowych a Internet rzeczy, profilowanie i repersonalizacja danych - Leja, Paulina (Wydawnictwo C.H. Beck, 2017)
The aim of the article is describing the Internet of Things and re-personalization of data with effects and threats which they may cause in the context of protection of the data. The author of the article compares them to the regulation included in the Regulation 2016/679 of 27 April 2016 of the European Parliament and the Council of the European Union on the protection of legal persons with regard to the processing of personal data and on the free movement of such data, and repealing the Directive 95/46/EC (General Data Protection Regulation).
Keywords: Internet of Things; re-personalization of data; Regulation (EU) 2016/679; General Data Protection Regulation; new technologies; anonymization of data